Prescribing roles in the employability of Malaysian graduates - Yoong, D.; Don, Z.M.; Foroutan, M. (Taylor & Francis, 2017)
In order to address the problems of graduate employability in Malaysia, the Malaysian Government produced in 2012, the National Graduate Employability Blueprint 2012–2017. In addition to setting out in detail the government’s philosophy and vision, the blueprint identifies key players who are expected to play crucial roles in making Malaysian graduates more employable. This research provides a critique of the assigned roles by comparing them with those reported in other scholarly research. It was found that the Malaysian Government expects institutions of higher learning (IHLs) to give priority to the needs of the industry, and to take full responsibility for preparing students for the demands of the workplace. This elevates the position of employers as powerful entities who set the direction for IHLs, and takes for granted that graduates need to be moulded by their IHLs before joining the workforce. Intriguingly, the blueprint does not assign any role to the family or the school, and it makes only limited reference to government agencies. In view of these assigned roles, the blueprint is likely to achieve limited success. Long-term planning needs to be more inclusive, and existing roles must be reassessed in order to make graduates more employable.